Single Nucleotide Polymorphisms and Osteoarthritis: An Overview and a Meta-Analysis. Issue 7 (February 2016) - Wang, Ting; Liang, Yuting; Li, Hong; Li, Haibo; He, Quanze; Xue, Ying; Shen, Cong; Zhang, Chunhua; Xiang, Jingjing; Ding, Jie; Qiao, Longwei; Zheng, Qiping
Abstract : Abstract: Osteoarthritis (OA) is a complex disorder characterized by degenerative articular cartilage and is largely attributed to genetic risk factors. Single nucleotide polymorphisms (SNPs) are common DNA variants that have shown promising and efficiency, compared with positional cloning, to map candidate genes of complex diseases, including OA. In this study, we aim to provide an overview of multiple SNPs from a number of genes that have recently been linked to OA susceptibility. We also performed a comprehensive meta-analysis to evaluate the association of SNP rs7639618 of double von Willebrand factor A domains (DVWA) gene with OA susceptibility. A systematic search of studies on the association of SNPs with susceptibility to OA was conducted in PubMed and Google scholar. Studies subjected to meta-analysis include human and case-control studies that met the Hardy–Weinberg equilibrium model and provide sufficient data to calculate an odds ratio (OR). A total of 9500 OA cases and 9365 controls in 7 case-control studies relating to SNP rs7639618 were included in this study and the ORs with 95% confidence intervals (CIs) were calculated. Over 50 SNPs from different genes have been shown to be associated with either hip (23), or knee (20), or both (13) OA. The ORs of these SNPs for OA and the subtypes are not consistent. As to SNP rs7639618 of DVWA, increased knee OA risk was observed in all genetic models analyzed. Specifically, people from Asian with G-allele showed significantly increased risk of knee OA (A versus G: OR = 1.28, 95% CI 1.13–1.46; AA versus GG: OR = 1.60, 95% CI 1.25–2.05; GA versus GG: OR = 1.31, 95% CI 1.18–1.44; AA versus GA+GG: OR = 1.34, 95% CI 1.12–1.61; AA+GA versus GG: OR = 1.40, 95% CI 1.19–1.64), but not in Caucasians or with hip OA. Our results suggest that multiple SNPs play different roles in the pathogenesis of OA and its subtypes; SNP rs7639618 of DVWA gene is associated with a significantly increased risk of knee OA in Asians. Given the limited sample size, further studies are needed to evaluate this observation.